Antihyperlipidemic, hypoglycaemic and antioxidative potential of Juglans Regia (walnuts) in an experimental animal model of dietary hyperlipidemia. - Sangi, Iqra; Shamim, Mufzala; Khan, Nazish Iqbal (International Journal of Endorsing Health Science Research, 2022)
Background: Cardiovascular diseases (CVD) are recognized as the world's primary cause of fatality, particularly in the developing countries. Stroke and ischemic heart disease have reportedly been the principal manifestations of vascular disease mainly because of the gradual increase in the incidence of the risk factors. In this aspect, the present study is planned to investigate the cardio-protective potential of Juglans regia (JR) (walnuts) consumption in controlling dyslipidemia. JR has notable therapeutic effects and, it has been used since ancient times for its anti-inflammatory, cardio-protective, and anti-bacterial properties. Methodology: In this study, 32 age-matched females, Wistar albino rats of 5-6 weeks weighing 200 g, were selected and equally divided into four experimental groups. Group I was used as control, Group II was positively induced hyperlipidemia through a high-fat diet; Group III animals were fed normal rat chow along with 153 mg JR powder, and Group IV animals have also inducted hyperlipidemia through a high-fat diet incorporated with 153 mg JR powder/Kg for 15 days. Bodyweight changes along with daily diet consumption were measured on alternate days. Results: In comparison to the control group, animals fed with a high-fat diet (Group II) showed a non-significant increase in plasma lipid profile, total cholesterol (TC), triglycerides (TG), and plasma high-density lipoprotein (HDL) levels. Group III and IV animals, after walnut powder supplementation, showed a significant decrease in lipid profile change in very Low-Density Lipoprotein levels (VLDL) of 10.3 ± 0.60 mg/dl and 12.27 ± 0.94 mg/dl together with nephron-protective & reno-protective enzymatic alterations. Histological analysis revealed signs of inflammation in high fat treated groups while well-maintained cardiac tissues within walnut treated groups, respectively. Conclusion: Daily consumption of Juglans Regia (walnut) in the dosage mentioned earlier is beneficial in protectively modulating dyslipidemia, hyperglycemic, and oxidative tissue potential of high-fat diet consumption in an experimental animal model.